2019
DOI: 10.1038/s41598-019-42188-9
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete cell disruption of resistant microbes

Abstract: Biomolecules for oMIC analysis of microbial communities are commonly extracted by bead-beating or ultra-sonication, but both showed varying yields. In addition to that, different disruption pressures are necessary to lyse bacteria and fungi. However, the disruption efficiency and yields comparing beadbeating and ultra-sonication of different biological material have not yet been demonstrated. Here, we show that ultra-sonication in a bath transfers three times more energy than bead-beating over 10 min. TEM imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The 18 O-CUE method relies on measurements of MBC ( Figure 1a) and microbial DNA ( Figure 1c) using methods known to underestimate the true values for microbes in the soil. For instance, DNA extraction yields changes depending on the method used (Martin-Laurent et al, 2001;Starke et al, 2019) and soil type (Martin-Laurent et al, 2001;Feinstein et al, 2009), with one company reporting up to 4 to 8Â higher yields with its newer kit compared to its predecessor (QIAGEN Germantown, MD, USA). DNA extraction efficiency may also preferentially capture one group of taxa over another, based on properties of cell walls and cell membranes or physical location within the soil that make them more or less susceptible to cell lysis (Starke et al, 2019).…”
Section: Literature Review To Set Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The 18 O-CUE method relies on measurements of MBC ( Figure 1a) and microbial DNA ( Figure 1c) using methods known to underestimate the true values for microbes in the soil. For instance, DNA extraction yields changes depending on the method used (Martin-Laurent et al, 2001;Starke et al, 2019) and soil type (Martin-Laurent et al, 2001;Feinstein et al, 2009), with one company reporting up to 4 to 8Â higher yields with its newer kit compared to its predecessor (QIAGEN Germantown, MD, USA). DNA extraction efficiency may also preferentially capture one group of taxa over another, based on properties of cell walls and cell membranes or physical location within the soil that make them more or less susceptible to cell lysis (Starke et al, 2019).…”
Section: Literature Review To Set Model Parametersmentioning
confidence: 99%
“…For instance, DNA extraction yields changes depending on the method used (Martin-Laurent et al, 2001;Starke et al, 2019) and soil type (Martin-Laurent et al, 2001;Feinstein et al, 2009), with one company reporting up to 4 to 8Â higher yields with its newer kit compared to its predecessor (QIAGEN Germantown, MD, USA). DNA extraction efficiency may also preferentially capture one group of taxa over another, based on properties of cell walls and cell membranes or physical location within the soil that make them more or less susceptible to cell lysis (Starke et al, 2019). There is some evidence that bacterial DNA is extracted more efficiently than fungal DNA (DNAexteffB vs. DNAexteffF, respectively; Feinstein et al, 2009;Starke et al, 2019), so we allow the values to vary separately from one another in our simulations.…”
Section: Literature Review To Set Model Parametersmentioning
confidence: 99%
“…It has also been suggested that ultrasonication (frequencies of greater than 20 kHz) may result in cell lysis, thereby releasing free genetic material into the sonicated solution that would not be dense enough to effectively pellet [ 72 , 73 ]. Specifically, Starke et al (2019) reported that ultrasonication for 10 min resulted in an unequal lysis of Gram-negative over Gram-positive or fungal cells, which would underrepresent less-resistant bacterial populations [ 72 ]. Comparatively, a study evaluating sonication in two different lysis buffers as methods for downstream extraction activities found that sonication for 20 min was insufficient to lyse cyanobacteria and release genetic material into the matrix [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two mL bioreactor liquid was centrifuged (3200× g , 10 min, 4 °C) and the pellet was solved in 1 mL lysis buffer (8M Urea, 2M Thiourea, 1 mM Phenylmethylsulfonylfluorid). Bacteria were disrupted by bead beating (FastPrep-24, MP Biomedicals, Sanra Ana, CA, USA; 5.5 ms, 1 min, 3 cycles) followed by ultra-sonication (UP50H, Hielscher, Teltow, Germany; cycle 0.5, amplitude 60%) and centrifugation (10,000× g , 10 min) [ 28 ]. The supernatant was used for protein concentration determination using the Pierce TM 660 nm Protein Assay (Thermo Scientific, Thermo Fischer Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%